2015
DOI: 10.4274/vhd.54227
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution Clinical and Demographic Features of HBsAg Positive Patients in Şanlıurfa Region

Abstract: ÖZObjective: The objective of this study was to investigate the distribution of the clinic and demographic characteristics of hepatitis b surface antigen (HBsAg) positive patients in Şanlıurfa region. 49±15 years, range: 20-73) and 24 (83%) were male. Seventeen patients (5%) (mean age: 37.8±12.8 years, range: 16-60) were antihepatitis D virus (anti-HDV) positive, 11 (65%) were male, 5 of them were in the cirrhotic stage. Two patients (0.6%) had HBV/HCV coinfection, two patients (0.6%) had hepatocellular carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…During the study period of 35 years, 111 publications were found 13–123 . Among inactive HBV carriers, 34 studies reported HDV prevalence and it did not change significantly over three decades 6,13–45 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the study period of 35 years, 111 publications were found 13–123 . Among inactive HBV carriers, 34 studies reported HDV prevalence and it did not change significantly over three decades 6,13–45 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Among inactive HBV carriers, 34 studies reported HDV prevalence and it did not change significantly over three decades 6,13–45 (Table 1). Among patients with chronic hepatitis, 50 studies reported decreasing (from Period 1 to Period 2) and then increasing (from Period 2 to period 3) HDV prevalence 9,13–18,20,22–27,29–33,35–65 . (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the risk of resistance is low, tenofovir disoproxil fumarate should be preferred (16). In our series of 296 HBsAg-positive patients whom we followed between Dec 2011 and Apr 2012 in the Şanlıurfa region, there were 7 pregnant patients (approximately 2%), and tenofovir was started in 3 of these patients in the last trimester because of the higher viral load (2). In our patient, severe hepatitis B was considered and tenofovir disoproxil fumarate therapy was started.…”
Section: Discussionmentioning
confidence: 99%
“…Şanlıurfa is in a HBV endemic region where birth rates increase each year (2). Pregnancy-specific liver diseases are responsible for approximately 60% of the liver diseases in pregnancy, whereas 40% of these diseases are caused by acute viral hepatitis (3,4).…”
Section: Introductionmentioning
confidence: 99%